KARYOMORPHOLOGY OF THE MORMYRID FISH Brevimyrus niger: THE SOLE REPRESENTATIVE OF THE GENUS Brevimyrus FROM OLUWA RIVER, NIGERIA - JEGEDE, O. I.; AKINTOYE, M. A. (Nigerian Journal of Fisheries, 2025)
The present study analysed the chromosome composition of the Brevimyrus niger population in the Oluwa River in Nigeria. It provides karyotypic data, including C- and AgNO banding, to describe its karyotype and highlight the differences between it and a previously studied Ethiopian population. Metaphase chromosomes were processed from the kidney following a peritoneal 0.05% colchicine injection at 1 ml per 100g of fish mass. The chromosome metaphase slide was stained with 6% Giemsa solution for 20 minutes; C-banding and location of the nucleolar organising region followed standard cytogenetic procedure. Karyotyping was done by classifying the metaphase chromosomes as metacentric, submetacentric, and acrocentric. Chromosome homologues were subsequently arranged in descending order of size. The diploid chromosome number, 2n = 48, included heteromorphic chromosomes comprised of a metacentric and an acrocentric. C-bands were positive at the centromere of all the chromosomes and the telomere of an acrocentric. The evolution of the karyotype probably involved the centric fission of a metacentric chromosome and the subsequent telomere telomere fusion of one of the fission products with an acrocentric while maintaining the chromosome number. While the Nigerian and the Ethiopian fish share the same diploid number of 2n = 48, the presence of heteromorphic chromosomes in the Nigerian fish differentiates it from its Ethiopian counterpart as a distinct population. However, the possibility of speciation within the Brevimyrus genus cannot be ruled out. The study contributes to understanding chromosome evolution in the family Mormyridae and demonstrates the significance of cytogenetics in discovering biodiversity in the Brevimyrus genus.